2016
DOI: 10.1653/024.099.0110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Antennal Sensilla Distribution Pattern on the Behavioral Responses ofTribolium castaneum(Coleoptera: Tenebrionidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
3
12
0
2
Order By: Relevance
“…However, the thickness of the cuticular wall was clearly different between the “thick‐walled” trichoid sensilla and the “thin‐walled” basiconic sensilla in the antennae of B. depressa , which appears to be in accordance with the observations in other groups of insects. For example, the single‐walled basiconic sensilla on the antennae of a fly, Ceratitis capitata (Tephritidae), were thin‐walled (Mayo, Anderson, Burguete, & Chillida, ), whereas the antennal trichoid sensilla in a beetle Tribolium castaneum (Tenebrionidae) were thick‐walled (Ali, Diakite, Ali, & Wang, ). It is not yet clear if this correlation is consistent across a wide range of insect species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the thickness of the cuticular wall was clearly different between the “thick‐walled” trichoid sensilla and the “thin‐walled” basiconic sensilla in the antennae of B. depressa , which appears to be in accordance with the observations in other groups of insects. For example, the single‐walled basiconic sensilla on the antennae of a fly, Ceratitis capitata (Tephritidae), were thin‐walled (Mayo, Anderson, Burguete, & Chillida, ), whereas the antennal trichoid sensilla in a beetle Tribolium castaneum (Tenebrionidae) were thick‐walled (Ali, Diakite, Ali, & Wang, ). It is not yet clear if this correlation is consistent across a wide range of insect species.…”
Section: Discussionmentioning
confidence: 99%
“…However, the thickness of the cuticular wall was clearly different between the "thick-walled" trichoid sensilla and Ceratitis capitata (Tephritidae), were thin-walled (Mayo, Anderson, Burguete, & Chillida, 1987), whereas the antennal trichoid sensilla in a beetle Tribolium castaneum (Tenebrionidae) were thick-walled (Ali, Diakite, Ali, & Wang, 2016). It is not yet clear if this correlation is consistent across a wide range of insect species.…”
Section: Fine Structure Of Olfactory Sensillamentioning
confidence: 99%
“…Red flour beetles may use the sensilla basiconica to detect sex pheromones, possibly in conjunction with host plant odors, as great numbers of sensilla can indicate high sensitivity levels (Chapman, 1998). In addition, the sensilla basiconica on the last 3 segments of the club might play a major role in the food source location behavior of T. castaneum (Ali et al, 2016). Accordingly, we recorded changes in the sensilla basiconica morphology in adult antennae after pupal UV-C radiation, and interestingly, the sensilla basiconica subtypes (sb1 and sb2) had a wider shape than the controls.…”
Section: Discussionmentioning
confidence: 80%
“…This study revealed a decrease in the number and length of several types of sensilla after UV-C radiation. In T. castaneum, the sensilla trichodea are responsible for the olfactory detection of host plants and mating sites (Ali et al, 2016). We found that the number and length of the st1 and st2 subtypes on the club, scape, and pedicel were reduced in the adults that were irradiated with UV-C during the pupal stage.…”
Section: Discussionmentioning
confidence: 80%
“…Even fewer studies analyze the internal structure and innervation of the sensilla (Moeck, 1967). Several studies deal with the involvement of the antennal sensory system in interspecies communication and behavioral responses in Coleoptera (Lopes, Marques & Araújo, 2005;Ali et al, 2016).…”
Section: Introductionmentioning
confidence: 99%